Non-Sterile to Sterile Compounding: An Unconventional Response During the COVID-19 Pandemic. (February 2023) - Belisle, Caryn D.; Anger, Kevin; Kanaan, Dareen; Rocchio, Megan A.; Triggs, Angela; Chacon, Pablo; Kwok, Keely; Cotugno, Michael; Morris, Charles A.; Fanikos, John
The drug supply chain has suffered many interruptions over the past decade. The COVID-19 pandemic exacerbated an already fragile infrastructure for supplying critical medications to hospitals and health-systems. The purpose of this paper is to provide insight to the history, thought-processes, and response to critical medication shortages during the COVID-19 pandemic, with a focus on hydromorphone infusions and the action steps taken to engage in non-sterile to sterile (NSTS) compounding. Over a period of 6 weeks, we compounded 1, 613 NSTS hydromorphone infusion bags. All lots were cleared for sterility, particulate, potency, and endotoxin testing by an outside FDA registered laboratory. We did not have any safety reports filed specific to the NSTS compounded hydromorphone infusion bags. Over a period of 15 weeks, 715 infusions were consumed. The drug supply chain suffers frequent interruptions and critical shortages, particularly in times of a natural disaster or a global pandemic. Non-sterile to sterile compounding is often associated with risks of inaccuracies, impurities, and contamination. There are instances in which non-sterile to sterile compounding is appropriate and should be considered in times of drug shortages to support the care of hospitalized patients.